2018
DOI: 10.1097/md.0000000000012783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-flow nasal cannula oxygen therapy vs conventional oxygen therapy on adult postcardiothoracic operation

Abstract: Introduction:The effect of high-flow nasal cannula (HFNC) on adult post cardiothoracic operation remains controversial. We conducted a meta-analysis of randomized controlled trials to evaluate the effect of HFNC and conventional oxygen therapy (COT) on postcardiothoracic surgery.Methods:A search was conducted in Embase, MEDLINE, Ovid, and Cochrane databases until December, 2017 for all the controlled study to compare HFNC with COT in adult postcardiothoracic surgery. Two authors extracted data and assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
(49 reference statements)
0
15
1
Order By: Relevance
“…This conclusion was confirmed by a meta-analysis of 4 studies, which also reported that HFNC significantly reduced the incidence of pulmonary complications. 44 However, the results of our meta-analysis were not identical to these 2 meta-analyses. Our meta-analysis included 8 randomized controlled trials and a larger sample size.…”
Section: Discussioncontrasting
confidence: 74%
“…This conclusion was confirmed by a meta-analysis of 4 studies, which also reported that HFNC significantly reduced the incidence of pulmonary complications. 44 However, the results of our meta-analysis were not identical to these 2 meta-analyses. Our meta-analysis included 8 randomized controlled trials and a larger sample size.…”
Section: Discussioncontrasting
confidence: 74%
“…Notwithstanding previous meta‐analyses published examining outcomes with HFNC compared with others forms of oxygen therapy in postoperative patients, our review, including the most recent study data, is the first to show improvements with HFNC strictly in all postoperative patients presenting with high risk for PCs. Of the previous reviews, two compared HFNC with COT in post‐extubation cardiac surgical patients which included two RCTs 39 or four RCTs, 40 respectively, and found reduction of the need for escalation of respiratory support compared with COT. These results were in accord with ours.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Because of these advantages, HFNC has been applied and has shown benefits in a number of clinical conditions, including hypoxemic respiratory failure, cardiogenic pulmonary edema, postoperation, and postextubation, and in subjects who have do-not-resuscitate (DNR) or do-not-intubate (DNI) orders. [8][9][10][11][12][13][14][15] In a recent large-scale study, HFNC was reported to decrease mortality in adult subjects with acute hypoxemic respiratory failure compared with noninvasive ventilation (NIV) and standard oxygen therapy. 16 However, in immunocompromised adult subjects with acute hypoxemic respiratory failure, there was no significant difference in mortality between HFNC and normal oxygen delivery.…”
Section: Introductionmentioning
confidence: 99%